OFD1: One gene, several disorders. Issue 1 (2nd February 2022) - Pezzella, Nunziana; Bove, Guglielmo; Tammaro, Roberta; Franco, Brunella
Abstract: The OFD1 protein is necessary for the formation of primary cilia and left–right asymmetry establishment but additional functions have also been ascribed to this multitask protein. When mutated, this protein results in a variety of phenotypes ranging from multiorgan involvement, such as OFD type I (OFDI) and Joubert syndromes (JBS10), and Primary ciliary dyskinesia (PCD), to the engagement of single tissues such as in the case of retinitis pigmentosa (RP23). The inheritance pattern of these condition differs from X‐linked dominant male‐lethal (OFDI) to X‐linked recessive (JBS10, PCD, and RP23). Distinctive biological peculiarities of the protein, which can contribute to explain the extreme clinical variability and the genetic mechanisms underlying the different disorders are discussed. The extensive spectrum of clinical manifestations observed in OFD1 ‐mutated patients represents a paradigmatic example of the complexity of genetic diseases. The elucidation of the mechanisms underlying this complexity will expand our comprehension of inherited disorders and will improve the clinical management of patients.